THE EFFECT OF CONSCRIPTION ON ARMED CONFLICT - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The study investigated the impact of Child Soldiers in Armed conflict with a particular reference to Central Equatoria state in South Sudan. The objectives of the study were to; examine the Relationship between Child soldiers and forced Recruitments in South Sudan, assess the indicators Child soldiers in South Sudan and to examine the relationship between forced Recruitments   and Armed conflict in south Sudan.The descriptive design using a case study of Central Equatoria State and both qualitative and quantitative approaches were used. The study population was 182. Sampling technique was purposive and simple random. The Sample size was 140 respondents from the employees and beneficiaries of Equatorial State in South Sudan and Data was analyzed using descriptive analysis option of SPSS version (20.0).The major findings of the study were that there is a significant positive correlation between; Child soldiers Armed conflict (r = 0.632, P-value < 0.01), forced Recruitment and conflict Armed(r = 0.512, P-value < 0.01) and the attributes explained 59% of the variance of child Soldier (R Square =.518) as the level to which they can predict the level of Armed Conflict in Central Equatorial State of South Sudan. Such that unit change in Child soldiers processes will contribute to a change in the possibility of Armed Conflict by (.581) while a one unit change in Forced Recruitments and Child soldiers will contribute to a change in the Armed Conflict in Central Equatorial State and other states of South Sudan (343). The study recommends that the State and Country leaders should develop foreign  relations with other international communities that aim at empowering people with education values and promoting an electoral process that serves the purpose of national renewal and peace commitment, need to make more use of an integrated application of litigation, alternative dispute resolution mechanisms and traditional justice systems in the management of natural resource conflicts and alternative Dispute Resolution mechanisms such as negotiation, fact finding facilitation and mediation should be adopted since they have the potential to enhance environmental justice since they allow parties to enjoy autonomy over the process and outcome; they are expeditious, cost-effective, flexible and employ non-complex procedures.